2020
DOI: 10.1155/2020/1517879
|View full text |Cite
|
Sign up to set email alerts
|

High Body Mass Index and Triglycerides Help Protect against Osteoporosis in Patients with Type 2 Diabetes Mellitus

Abstract: Purpose. This study was conducted to investigate whether high body mass index (BMI) and triglycerides (TGs) were protective factors for reducing osteoporosis (OP) in patients with type 2 diabetes mellitus (T2DM). Participants and Methods. Seventy-nine patients (aged 20 to 81) with T2DM were included in the study. Basic information and blood indicators were collected. Bone mineral density was used to diagnose OP. Participants were grouped according to BMI (normal weight vs. overweight/obese participants), TG (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Total osteocalcin levels . Total osteocalcin levels were reported in 29 studies [ 21 , 53 , 60 , 62 65 , 68 , 74 , 76 , 77 , 80 , 81 , 84 , 92 , 97 , 105 , 107 , 119 , 126 , 129 , 135 , 144 , 146 , 147 , 151 , 153 , 166 , 175 ], including 6,332 participants. Obesity was not associated with any difference in osteocalcin levels between individuals with and without obesity ( S7 Fig ), except in studies combining men and women (n = 9: MD = -3.86 ng/ml, 95% CI: -6.78, -0.95, P = 0.009, I 2 = 97%).…”
Section: Resultsmentioning
confidence: 99%
“…Total osteocalcin levels . Total osteocalcin levels were reported in 29 studies [ 21 , 53 , 60 , 62 65 , 68 , 74 , 76 , 77 , 80 , 81 , 84 , 92 , 97 , 105 , 107 , 119 , 126 , 129 , 135 , 144 , 146 , 147 , 151 , 153 , 166 , 175 ], including 6,332 participants. Obesity was not associated with any difference in osteocalcin levels between individuals with and without obesity ( S7 Fig ), except in studies combining men and women (n = 9: MD = -3.86 ng/ml, 95% CI: -6.78, -0.95, P = 0.009, I 2 = 97%).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that a high BMI and TG levels protected against osteoporosis, and these patients tended to have higher vitamin D levels. 8 Additionally, with extension of the course of DM, pancreatic function showed a downward trend, from the state of IR to the stage of insulin secretion disorder. Regression analysis showed that 25OHD and the IR index were not associated when we adjusted for no or some confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Both T2DM and osteoporosis are chronic disorders which are associated with severe morbidity and increased mortality. 4 Although there are a few previous studies which reported increased BMI declines the risk of osteoporosis in patients with diabetes mellitus, 5 , 6 it seems that available evidence on the association between obesity indices and bone mineral density (BMD) or risks of osteoporosis was controversial. A lot of previous studies showed a positive correlation between BMI and BMD, 6 while several other studies suggested that obesity was a risk factor for certain fractures.…”
Section: Introductionmentioning
confidence: 99%